Faktor yang Mempengaruhi Manajemen Laba pada Perusahaan Sub Sektor Pariwisata, Hotel dan Restoran - Rohma, Miftakhul; Pertiwi, Dwi Ari (Universitas Malahayati, 2025)
The purpose of the study was to recognise more in-depth factors related to Earnings Management in tourism, hotel and restaurant sub-sector companies. This research approach uses quantitative with secondary data sources. The focus of this research is on companies in the Tourism, Hotel and Restaurant sub-sectors. The data collection technique used was purposive sampling, so that the sample obtained in this study amounted to 25 companies in the Tourism, Hotel and Restaurant sub-sectors listed on the Indonesia Stock Exchange in 2022-2023. The research results (t test) Bonus Compensation, Leverage, and Company Size partially affect Earnings Management. The results of the study (F test) Bonus Compensation, Leverage, and Company Size simultaneously affect Earnings Management.